RADIO FREQUENCY AND CHANNEL INVESTIGATION USING SOFTWARE-DEFINED RADIO IN MATLAB AND SIMULINK ENVIRONMENT (Nigerian Journal of Technology, 2018)
This paper is a four section investigation of various communication principles to demonstrate the capabilities of using MATLAB and Software Defined Radio (RTL-SDR R820T) to receive, decode, analyse and resample a radio frequency signal. A novel MATLAB model system is developed to identify signals based on the signal characteristics in the spectrum analysers. The bandwidth, frequency, modulation and demodulation techniques of the signal were also identified. The section two is a design developed around multiplex and down-conversion to baseband In-phase/Quadrature phase (IQ) for multiple channel Frequency Modulated (FM) and Amplitude Modulated Double Sideband Transmitted Carrier (AM-DSB-TC) signal received. The functional description of sampling, decimation and interpolation form part of the contribution of this paper. The final section of the paper presents a short research on the potential benefits and a survey into the future of Software Defined Radio (SDR). http://dx.doi.org/10.4314/njt.v37i4.26